ANALISIS PEMASARAN TEMPE PADA INDUSTRI RUMAH TANGGA â€œMULTI BAROKAHâ€ DI KOTA PALU - Nilawati, Iyut (AGROTEKBIS, 2015)
Marketing is all the activities related to the business of marketing products, including related marketing agencies path before it reached the hands of consumers, tempeh is almost always through intermediaries. Path traversed by the products of producers with or without intermediaries to reach the consumers known to form marketing channels. Tempe sold with a simple form of marketing channels, starting from middlemen, retailers up to end consumers. This study aims to determine the form of marketing channels tempe on Home Industry "Multi Barokah" in the city of Palu, knowing the amount of margin and efficiency of marketing tempe on Home Industry "Multi Barokah" in Palu. Respondent committed intentionally (purposive) that one person led to the consideration that the respondents know everything related to the company, especially marketing. Determination respondents traders used assessment method (Tracing Method), in order to obtain each of 4 people middlemen and retailers. The results showed that there are three forms of marketing channels tempe on Home Industry "Multi Barokah" in Palu, a) Producers à Middlemen à Retailers à Consumers, b) Producers à Middlemen à Consumers, c) Producers à Retailers à Consumers. Total margin on the first line of Rp.2.000 for the second line of  Rp.1.000 and the total margin for the third channel of Rp.2.500 Part of the price received by producers in the first marketing channels by 80% for the second line of 88.89% and part of the price received by producers for the third marketing channels by 80%, it indicates that part of the price received by producers on both channels is greater than the first and third channels. The results showed also that the value of the first channel marketing efficiency 9.50% the second channel at 11.66% and the marketing efficiency  value for the third channel of 7.27%. The value of the efficiency of the three marketing channels shows that the third channel is more efficient than the first and second channels.